2013
DOI: 10.1371/journal.pone.0073294
|View full text |Cite
|
Sign up to set email alerts
|

The AP-1 Transcription Factor c-Jun Prevents Stress-Imposed Maladaptive Remodeling of the Heart

Abstract: Systemic hypertension increases cardiac workload and subsequently induces signaling networks in heart that underlie myocyte growth (hypertrophic response) through expansion of sarcomeres with the aim to increase contractility. However, conditions of increased workload can induce both adaptive and maladaptive growth of heart muscle. Previous studies implicate two members of the AP-1 transcription factor family, junD and fra-1, in regulation of heart growth during hypertrophic response. In this study, we investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 69 publications
3
51
0
Order By: Relevance
“…On the other hand, JunD protects cardiomyocytes from undergoing apoptosis and hypertrophy by inhibiting AP-1 activity [14,15]. More recently, c-Jun was found to play a protective role in pressure overload maladaptive cardiac hypertrophy [16]. Collectively, these studies demonstrate that the AP-1 transcription factor targets gene programs that both induce and suppress apoptosis and hypertrophy, depending on AP-1 complex composition, expression level and the specific insult exerted.…”
Section: Introductionmentioning
confidence: 83%
“…On the other hand, JunD protects cardiomyocytes from undergoing apoptosis and hypertrophy by inhibiting AP-1 activity [14,15]. More recently, c-Jun was found to play a protective role in pressure overload maladaptive cardiac hypertrophy [16]. Collectively, these studies demonstrate that the AP-1 transcription factor targets gene programs that both induce and suppress apoptosis and hypertrophy, depending on AP-1 complex composition, expression level and the specific insult exerted.…”
Section: Introductionmentioning
confidence: 83%
“…MEF2 has a well-established role in sarcomere organization, because it regulates key target genes associated with the costamere and sarcomeric proteins (Ewen et al, 2011;Hinits and Hughes, 2007;Potthoff et al, 2007). There are fewer studies that have investigated the role of AP-1 in sarcomere integrity; however, in cardiomyocytes c-Jun has been shown to have an important role in promoting sarcomere gene expression and sarcomere integrity (Windak et al, 2013). Interestingly, destabilization of the actin cytoskeleton triggers cJun activity in vitro and represses glucocorticoid receptor activity (Oren et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, although loss of MEF2 and AP-1 have been implicated in loss of sarcomere integrity during development and satellite cell-mediated muscle regeneration (Hinits and Hughes, 2007;Potthoff et al, 2007;Windak et al, 2013), the combined role of these factors in muscle atrophy has not been investigated. Here, we document that MEF2 and AP-1 regulate several genes associated with the actin cytoskeleton.…”
Section: Introductionmentioning
confidence: 99%
“…1987). c-Jun has recently been shown to prevent myocardial fibrosis and cardiomyocyte apoptosis in cardiac adverse remodeling (Windak et al 2013). The kinases classically associated with c-Jun phosphorylation belong to the c-Jun N-terminal kinase (JNK) family, although c-Jun can also be phosphorylated through Erk 1/2 signaling (Leppä et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, while in BN rats radiation induced phosphorylation of extracellular signal-regulated kinase (Erk) 1/2, a mitogen-activated protein kinase known for its beneficial effects in the heart (Das et al 2009), Erk 1/2 phosphorylation was not observed in BN/Ka animals. Similarly, kininogen-deficiency prevented radiation-induced phosphorylation of c-jun, a transcription factor that has recently been shown to reduce adverse cardiac remodeling (Windak et al 2013). Here, we investigate the role of the B2 receptor in signaling events and inflammatory infiltration leading up to adverse remodeling in the irradiated heart by blocking the receptor pharmacologically using the bradykinin analog, HOE-140 (icatibant), a B2 receptor-selective antagonist (Wirth et al 1991).…”
Section: Introductionmentioning
confidence: 99%